SISTEM PENDIDIKAN DI NEGARA IRAN - Abdul Wahab Syakharani; Ahmad Rafi’i; Anif Ramadhani; Dilah Dilah; Khairul Muhsinin (ADIBA : JOURNAL OF EDUCATION, 2022)
The Islamic Republic of Iran (or Persia) is a Middle Eastern country located in Southwest Asia. Iran is one of the founding members of the United Nations (UN), Organization of the Islamic Conference (OIC), and the Non-Aligned Movement. The political system in Iran is based on a constitution called the "Qanun-e Asasi" (Basic Law). After the Iranian Islamic Revolution in 1979, the Iranian education system underwent a very basic change and all educational efforts had to be adapted to Islamic principles. Priority must be placed on ensuring efforts to educate children and the younger generation so that they become consistent Muslims and have a high commitment to the religion of Islam.